Volume 7: Turbomachinery, Parts A, B, and C 2011
DOI: 10.1115/gt2011-46332
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Stall Inception in Centrifugal Compressor Vaned Diffusers

Abstract: In compression systems the stable operating range is limited by rotating stall and/or surge. Two distinct types of stall precursors can be observed prior to full scale instability: the development of long-wavelength modal waves or a short-wavelength, three-dimensional flow breakdown (so-called “spike” stall inception). The cause of the latter is not well understood; in axial machines it has been suggested that rotor blade-tip leakage flow plays an important role, but spikes have recently been observed in shrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…For example, Everitt et al [10] reported the similar unsteady vortices at the diffuser leading edge in a high speed centrifugal compressor, as with the case of our paper. Furthermore, we confirmed that the LEV had the same form at high speed and the size of the LEV was increased at low mass flow late by CFD analysis, as we have mentioned in our previous paper [12].…”
Section: Structure Of Diffuser Stallsupporting
confidence: 72%
See 1 more Smart Citation
“…For example, Everitt et al [10] reported the similar unsteady vortices at the diffuser leading edge in a high speed centrifugal compressor, as with the case of our paper. Furthermore, we confirmed that the LEV had the same form at high speed and the size of the LEV was increased at low mass flow late by CFD analysis, as we have mentioned in our previous paper [12].…”
Section: Structure Of Diffuser Stallsupporting
confidence: 72%
“…For example, Spakovszky reported that four-cell backward travelling modal waves occur in the vaneless space prior to the surge [9]. Everitt et al reported the generation mechanism of spike stall inception by numerical analysis [10]. The short wavelength stall inception in centrifugal compressors with vaned diffusers was caused by the separation on the shroud side of the diffuser leading edge and radial flow reversal throughout the vaneless space.…”
Section: Introductionmentioning
confidence: 99%
“…The CFD setup of this work follows guidelines presented by Everitt [15]. Structural hexahedra, multi-block grids are automatically generated in the "AutoGrid" environment.…”
Section: General Description Of Cfd Calculationsmentioning
confidence: 99%
“…The Spalart-Allmaras turbulence model is used following successful application in past work [19]. According to best practice, y+ ranges from 1-10 for the first cell off the wall.…”
Section: Computational Approachmentioning
confidence: 99%